1999
DOI: 10.1021/bi990247c
|View full text |Cite
|
Sign up to set email alerts
|

Arg304 of Human DNA Primase Is a Key Contributor to Catalysis and NTP Binding:  Primase and the Family X Polymerases Share Significant Sequence Homology

Abstract: Comparison of the amino acid sequences of eucaryotic DNA primase and the family X polymerases indicates that primase shares significant sequence homology with this family. With the use of DNA polymerase beta (pol beta) as a paradigm for family X polymerases, these homologies include both the catalytic core domain/subunit of each enzyme (31 kDa domain of pol beta and p49 subunit of primase) as well as the accessory domain/subunit (8 kDa domain of pol beta and p58 subunit of primase). To further explore these ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 33 publications
5
61
0
Order By: Relevance
“…The location of the binding site for the initiating NTP has not been defined yet. It has been shown that the triphosphate group of the initiating nucleotide is important for dinucleotide synthesis, and it was proposed that it interacts with Arg-304 of p49 (35). However, recent structural data indicate that Arg-304 is buried inside the molecule and, accordingly, most likely plays a purely structural role; this explains the serious defect in primase activity when it is changed to another amino acid (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The location of the binding site for the initiating NTP has not been defined yet. It has been shown that the triphosphate group of the initiating nucleotide is important for dinucleotide synthesis, and it was proposed that it interacts with Arg-304 of p49 (35). However, recent structural data indicate that Arg-304 is buried inside the molecule and, accordingly, most likely plays a purely structural role; this explains the serious defect in primase activity when it is changed to another amino acid (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Because this mutation eliminated the ability of LEF-1 to function in transient-replication assays (13), the essential function of LEF-1 in baculovirus replication is directly connected with the primase activity. Interestingly, the three aspartates in mouse primase (D109, D111, and D306) align precisely with similar residues in the 31-kDa domain of DNA polymerase ␤, suggesting that Pri-type primases are probably members of the Pol X polymerase family (24). The three aspartates (D95, D97, and D280) in the archaeon Pyrococcus furiosus (Pfu) primase could be superimposed with the activesite residues of four different DNA polymerases, including human DNA polymerase ␤, indicating similar three-dimensional arrangements in all five structures (3).…”
Section: Vol 76 2002mentioning
confidence: 86%
“…This motif is also found in primases from a number of herpesviruses, phage T7, Saccharomyces cerevisiae, archaea, and mammals (3,24). Experimental data suggest that the two proximal aspartates in this motif are important for enzymatic activity.…”
Section: Vol 76 2002mentioning
confidence: 93%
“…The DNA replication of ⌽X174 ssDNA was carried out in a reaction mixture containing 66 ng of ⌽X174 ssDNA (New England Biolabs); 20 mM Tris-acetate (pH 7.3); 5 mM magnesium acetate; 20 mM potassium acetate; 1 mM dithiothreitol; 0.1 mg of bovine serum albumin (BSA)/ml; 1 mM ATP; 0.1 mM (each) CTP, GTP, UTP, dATP, dCTP, dGTP, and TTP; and 0.1 mM [␣- 32 (70,71). The reaction mixture was assembled on ice, and the reaction was started by the addition of pol-prim.…”
Section: Methodsmentioning
confidence: 99%
“…The replication of PyV DNA in vitro was performed according to methods described previously (6,57). Briefly, the assay contained 1.2 g of PyV Tag, 250 ng of pUC-Py1 DNA (PyV origin DNA [52]), and 200 g of S100 or depleted S100 extract in 30 mM HEPES-KOH (pH 7.8); 1 mM dithiothreitol; 7 mM magnesium acetate; 1 mM EGTA (pH 7.8); 4 mM ATP; 0.3 mM (each) CTP, GTP, and UTP; 0.1 mM (each) dATP and dGTP; 0.05 mM (each) dCTP and dTTP; 40 mM creatine phosphate; 80 g of creatine kinase/ml, and 5 Ci each of [␣ 32 P]dCTP and [␣ 32 P]dTTP (3,000 Ci/mmol; Amersham Pharmacia Biotech); pol-prim was added as indicated. The incorporation of radioactive dNMP was measured by acid precipitation of DNA and scintillation counting.…”
Section: Methodsmentioning
confidence: 99%